Atmospheric-Pressure Plasma Spray Deposition of Silver/HMDSO Nanocomposite on Polyamide 6, 6 with Controllable Antibacterial Activity. Issue 3 (May 2020) - Ribeiro, A. I.; Modic, M.; Cvelbar, U.; Dinescu, G.; Mitu, B.; Nikiforov, A.; Leys, C.; Kuchakova, I.; Souto, A. P.; Zille, A.
Novel coatings containing silver nanoparticles (AgNPs) with strong bonding and controllable antibacterial activity on polyamide 6, 6 fabric were produced by dielectric barrier discharge (DBD) plasma-assisted deposition at atmospheric pressure and hexamethyldisiloxane (HMDSO) layers. Silver ion release was tuned using a "sandwich" coating structure to prolong the antibacterial effect. The novel spray-assisted deposition increased deposition rates of AgNPs using atmospheric pressure DBD plasma treatment when an HMDSO layer was applied. An increase in AgNPs deposition in plasma treated samples and antimicrobial activity against Gram-negative ( Escherichia coli ) for samples with an additional HMDSO layer was observed. These coatings allow the development of new and safe wound dressings able to switch the antimicrobial effect against Gram-positive and Gram-negative bacteria by washing the dressing at high temperature (75 °C) before application.